Physical Exercise in Aquatic Environment and its Role in Phase III of a Cardiac Rehabilitation Program - Albuquerque, Nelson; Serviço de Medicina Fisica e de Reabilitação, Centro Hospitalar Tondela Viseu, Viseu, Portugal (2021)
Introduction: The benefits of land-based aerobic physical training in patients with cardiac pathology are well studied. However, there are patients who, for personal reasons or osteoarticular limitations, prefer to exercise in water, so it is important to understand the advantages, disadvantages and precautions to be taken when the rehabilitation plan is carried out in an aquatic environment.Methods: To carry out this narrative review, the following databases were accessed: MEDLINE, SCOPUS and Web of Science.Results:With the increase of the immersion depth, the heart fills and consequent systolic volume increases, but the heart rate (HR) decreases. Peak oxygen uptake (VO2peak) and HRpeak values are 84% and 95% lower in water compared to those observed out of water, respectively. Therefore, a reduction of 13% or 10 bpm in relation to the target HR values established out of water is recommended. Aquatic exercise induces an increase in heart rate variation and cardiac autonomic modulation, both of which have a positive impact on the prognosis of these patients.Conclusion: Physical exercise in water is safe, provides cardiovascular protection and improves the prognosis in low-risk cardiac patients who are in phase III of the cardiac rehabilitation program and who, for musculoskeletal or personal reasons, prefer to perform exercise in this context.